Process, sensemaking, and organizing - Hernes, Tor; Maitlis, Sally (Perspectives on process organization studies, 2010)
This volume brings together perspectives on process theories, an emerging approach to the study of organizations that focuses on (understanding) activities, interactions, and change as essential properties of organizations rather than structures and state.